Bonding paste, bonded body using same, and method for manufacturing bonded body

A bonding paste with a polyamide and specific metal particles addresses the issues of poor dispersibility and stress concentration in existing materials, providing high bonding strength and thermal cycle resistance.

JP7613286B2Active Publication Date: 2025-01-15TOYO INK MFG CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021102687
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-21
Publication Date
2025-01-15
Estimated Expiration
2041-06-21

AI Technical Summary

Technical Problem

Existing bonding materials, such as those described in Patent Documents 1 and 2, suffer from poor dispersibility and coatability, leading to insufficient bonding strength and cracking under thermal cycles due to stress concentration when used with materials like silicon carbide, which have a small coefficient of linear expansion.

Method used

A bonding paste comprising a polyamide with phenolic hydroxyl groups and specific metal particles of 100 to 350 nm diameter, combined with a dispersion medium, to form a dense coating film that suppresses voids and maintains bonding strength through thermal cycles.

Benefits of technology

The bonding paste achieves high bonding strength and resistance to thermal cycles, even with rigid materials, by ensuring a dense coating film without voids and maintaining strength during cooling and heating cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007613286000009
    Figure 0007613286000009
  • Figure 0007613286000001
    Figure 0007613286000001
  • Figure 0007613286000002
    Figure 0007613286000002
Patent Text Reader

Abstract

To provide a paste for joining having excellent joining strength and capable of maintaining the joining strength after a thermal cycle, and to provide a joined body using the paste for joining and having excellent joining strength and thermal cycle resistance, when using an adherend having small linear expansion coefficient and being rigid.SOLUTION: A paste for joining contains: a specific polyamide having a phenolic hydroxyl group in a side chain thereof; metal particles with a particle diameter (d50) corresponding to 50% of a cumulative particle diameter distribution of 100-350 nm; and a dispersant.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a metal particle-containing composition, a bonding paste, and a bonded body. [Background technology]

[0002] Conventionally, solder has been used as a joining material for joining metal members together, between a metal member and a semiconductor element, or between a metal member and an LED element, etc. In recent years, in the field of next-generation power electronics, there has been a demand for alternatives to solder as a joining material for devices such as SiC that can operate at high temperatures from the viewpoint of high-temperature operation reliability, and for example, the use of joining pastes using metal particles has been proposed as shown in Patent Documents 1 and 2.

[0003] Patent Document 1 discloses a bonding agent that contains metal particles, a polyamide that is a polymer of a polybasic acid monomer and a polyamine monomer and has phenolic hydroxyl groups in its side chains, and a tri- or higher functional compound that can react with the phenolic hydroxyl groups.

[0004] Patent Document 2 discloses a bonding material that contains metal submicron particles with an average primary particle size of 0.5 to 3.0 μm and metal nanoparticles with an average primary particle size of 1 to 200 nm that are coated with an organic compound having 6 to 8 carbon atoms. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2017-137375 A [Patent Document 2] JP 2011-80147 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, the bonding agent described in Patent Document 1 has problems with applicability due to insufficient dispersibility of metal particles, and therefore the coating film after application has poor smoothness and leveling properties, and the film is not dense enough, resulting in poor bonding strength, which decreases with thermal cycling. Furthermore, the bonding material described in Patent Document 2 has a problem in that the bonding strength at the bonded portion is poor and decreases with thermal cycles. Furthermore, the bonding materials described in Patent Documents 1 and 2 have a problem that when an adherend is a material (e.g., silicon carbide (hereinafter, referred to as SiC)) that has a smaller linear expansion coefficient and is more rigid than the metal that is the main component of the bonding material, stress is concentrated in the bonding coating during a thermal cycle test, and the bonding coating cannot withstand the resulting stress, causing cracks. In other words, the problem to be solved by the present invention is to provide a bonding paste that has excellent bonding strength and can maintain its bonding strength even after thermal cycling when an adherend having a small linear expansion coefficient and a rigidity is used, and a bonded body using the bonding paste that has excellent bonding strength and resistance to thermal cycling. [Means for solving the problem]

[0007] The present invention relates to a bonding paste containing a polyamide (A), which is a polymer of a polybasic acid monomer and a polyamine monomer and has a phenolic hydroxyl group in a side chain, metal particles (B), and a dispersion medium (C), in which the polyamide (A) satisfies the following (i) and / or (ii), and the metal particles (B) are particles having a particle size (d50) corresponding to 50% of an accumulated particle size distribution of 100 to 350 nm. (i) The polyamide (A) is a polyamide (A-1) in which the phenolic hydroxyl group and the hydrocarbon group having 20 to 60 carbon atoms (but excluding the aromatic ring to which the phenolic hydroxyl group is bonded) are contained within the same polymer. (ii) The polyamide (A) is a polyamide (A-3) which is a mixture of a polyamide (a-1) having a phenolic hydroxyl group in the side chain and a polyamide (a-2) having a hydrocarbon group having 20 to 60 carbon atoms.

[0008] The present invention also relates to the above-mentioned bonding agent, wherein the content of the polyamide (A) is in the range of 0.01 to 1.70 mass % based on the mass of the metal particles (B).

[0009] The present invention also relates to the above-mentioned joining paste, wherein the metal particles (B) are particles having a particle diameter (d1) corresponding to 1% of the cumulative particle diameter distribution of 30 to 200 nm and a particle diameter (d99) corresponding to 99% of the cumulative particle diameter distribution of 300 to 900 nm.

[0010] The present invention also relates to the above bonding paste, wherein the metal particles (B) are particles having a mass reduction rate of 0.5 to 7.0 mass %.

[0011] The present invention also relates to a bonded body in which a first body to be bonded and a second body to be bonded are bonded with the bonding paste.

[0012] The present invention further relates to a method for producing a bonded body, comprising applying the bonding paste to a first body to be bonded and placing a second body to be bonded on the applied surface. Effect of the Invention

[0013] According to the present invention, it is possible to provide a metal particle-containing composition and a bonding paste that have high bonding strength at a bonding portion and that do not decrease with thermal cycles. It is also possible to provide a bonded body that does not deteriorate with thermal cycles. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a schematic diagram showing a DTA curve and a TG curve during heating of the metal particles of the present invention, which are measured using a simultaneous differential heat-thermogravimetry analyzer (TG-DTA). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The bonding paste of the present invention contains polyamide (A), which is a polymer of a polybasic acid monomer and a polyamine monomer and has a phenolic hydroxyl group in a side chain, metal particles (B), and a dispersion medium (C), characterized in that the polyamide (A) satisfies the following (i) and / or (ii), and the metal particles (B) are particles having a particle size (d50) corresponding to 50% of the cumulative particle size distribution of 100 to 350 nm. (i) The polyamide (A) is a polyamide (A-1) in which the phenolic hydroxyl group and the hydrocarbon group having 20 to 60 carbon atoms (but excluding the aromatic ring to which the phenolic hydroxyl group is bonded) are contained within the same polymer. (ii) The polyamide (A) is a polyamide (A-3) which is a mixture of a polyamide (a-1) having a phenolic hydroxyl group in the side chain and a polyamide (a-2) having a hydrocarbon group having 20 to 60 carbon atoms. By using a combination of a specific polyamide (A) and metal particles (B) having a particle size (d50) of 100 to 350 nm corresponding to 50% of the cumulative particle size distribution, not only is excellent coating property achieved, but the occurrence of voids in the bonded coating film is suppressed, enabling the formation of a dense coating film, resulting in excellent bonding strength and cycle characteristics. The present invention will be described in detail below. In the following description, the parentheses for a hydrocarbon group having 20 to 60 carbon atoms (excluding the aromatic ring to which the phenolic hydroxyl group is bonded) may be omitted, but when a "hydrocarbon group having 20 to 60 carbon atoms" is written, it is assumed that the condition in the parentheses is satisfied. In addition, a "hydrocarbon group having 20 to 60 carbon atoms" may be written as a "C20 to 60 hydrocarbon group".

[0016] <Metal particles (B)> The bonding paste of the present invention contains metal particles (B) having a particle diameter (d50) corresponding to 50% of the cumulative particle diameter distribution of 100 to 350 nm. Examples of the metal in the metal particles (B) include gold, silver, copper, nickel, chromium, palladium, rhodium, ruthenium, indium, silicon, aluminum, tungsten, molybdenum, platinum, and alloys thereof. In addition, fine particles coated with a core and a material different from the core material, specifically, for example, silver-coated copper powder, in which the core is copper and the surface is coated with silver, can be mentioned. In addition, powders of metal oxides such as silver oxide, indium oxide, tin oxide, zinc oxide, ruthenium oxide, ITO (tin-doped indium oxide), AZO (aluminum-doped zinc oxide), and GZO (gallium-doped zinc oxide), as well as powders surface-coated with these metal oxides can be mentioned. The type of metal used may be one type, or two or more types may be used in combination.

[0017] In the present invention, it is important to use metal particles (B) that are particles having a particle size (d50) corresponding to 50% of the cumulative particle size distribution of 100 to 350 nm. From the viewpoint of suppressing the generation of voids and exerting high bonding strength, and from the viewpoint of sufficiently promoting melting and integration (hereinafter, also referred to as sintering) between the metal particles and suppressing a decrease in bonding strength after thermal cycles, d50 of the metal particles (B) is preferably 120 to 300 nm, and more preferably 180 to 300 nm.

[0018] Moreover, the metal particles (B) preferably have a size (particle diameter) distribution, and are preferably particles with a particle diameter (d1) corresponding to 1% of the cumulative particle diameter distribution and a particle diameter (d99) corresponding to 99% of the cumulative particle diameter distribution controlled. By having the metal particles (B) have a particle diameter distribution, it is possible to effectively fill the gaps between the metal particles, and the occurrence of voids in the bonded coating film is further suppressed, which is preferable. The d1 of the metal particles (B) is preferably from 30 to 200 nm, more preferably from 40 to 180 nm, and further preferably from 50 to 150 nm. The d99 of the metal particles (B) is preferably from 300 to 900 nm, more preferably from 300 to 750 nm, and further preferably from 350 to 600 nm.

[0019] The 1% cumulative particle size distribution particle size (d1), 50% cumulative particle size distribution particle size (d50), and 99% cumulative particle size distribution particle size (d99) of the metal particles (B) were measured for the dispersion obtained by dispersing the metal particles (B) in an organic solvent (IPA: isopropyl alcohol) to a concentration of 0.5% by mass using an ultrasonic disperser. For example, Nanotrac UPA-EX150 (manufactured by Nikkiso Co., Ltd.) can be used for the measurement. In this specification, the 1% cumulative particle size distribution particle size (d1), 50% cumulative particle size distribution particle size (d50), and 99% cumulative particle size distribution particle size (d99) refer to particle sizes (volume basis) corresponding to 1%, 50%, and 99% of the cumulative particle size distribution, respectively.

[0020] The surfaces of the metal particles (B) are preferably coated with an organic component (b). Examples of the organic component (b) include fatty acids, aliphatic amines, and aliphatic alcohols. Preferably, it is a saturated or unsaturated fatty acid, more preferably, it is a saturated or unsaturated fatty acid having 3 to 22 carbon atoms, and even more preferably, it is a saturated or unsaturated fatty acid having 6 to 18 carbon atoms. The organic component (b) may contain one or more kinds.

[0021] In the present invention, the metal particles (B) have a d50 of 100 to 350 nm, so that an excessive amount of the organic component (b) is not required, and the organic component is prevented from remaining in the bonding material, thereby preventing the generation of voids and providing high bonding strength. Furthermore, the metal particles (B) in the present invention have a d50 of 100 to 350 nm, so that the melting point is not too high, and as a result, sintering between the metal particles proceeds sufficiently without excessively high temperatures, a dense bonding coating film is formed, and a decrease in bonding strength after thermal cycling can be suppressed.

[0022] The metal particles (B) have a mass reduction rate of preferably 0.5 to 7.0% by mass, more preferably 1.0 to 5.0% by mass, and further preferably 2.0 to 4.0% by mass. A mass reduction rate of the metal particles (B) of 0.5% by mass or more is preferable because it can prevent the bonding paste from becoming too viscous, provide good coating performance, form a dense bonding coating film, and provide good bonding strength. On the other hand, a mass reduction rate of the metal particles (B) of 7.0% by mass or less is preferable because it can prevent the organic component (b) from remaining after sintering, prevent the generation of voids in the bonding coating film, and provide good bonding strength.

[0023] The method for calculating the mass reduction rate will be described below. As shown in Figure 1, the start temperature Ts of the lowest exothermic peak shown in the DTA curve represents the extrapolated start temperature, and is the temperature at the intersection of a straight line extending the baseline on the low temperature side toward the high temperature side in the heating measurement with a tangent drawn on the curve of the lowest exothermic peak on the low temperature side at the point where the gradient is maximum. Similarly, the end temperature Te of the highest exothermic peak shown in the DTA curve represents the extrapolated end temperature, and is the temperature at the intersection of a straight line extending the baseline on the high temperature side toward the low temperature side in the heating measurement with a tangent drawn on the curve of the highest peak on the high temperature side at the point where the gradient is maximum. It is believed that the decomposition of organic component (b) begins at the extrapolated onset temperature Ts of the lowest exothermic peak, the mass of the metal particles begins to decrease, and the decomposition of organic component (b) ends at the extrapolated end temperature Te. Therefore, Ts is also called the decomposition onset temperature, and Te is also called the decomposition end temperature. That is, the mass reduction rate is expressed by the following formula. Mass reduction rate = [(mass of metal particles (B) at Ts - mass of metal particles (B) at Te) / mass of metal particles (B) at Ts] x 100 In the above formula, "the mass of the metal particles (B) at Ts - the mass of the metal particles (B) at Te)" is understood to be the amount of the organic component (b). Although some mass loss of metal particles may be observed in the region lower than Ts or higher than Te, if no clear exothermic peak is observed, it is understood that this is not due to decomposition.

[0024] The metal particles (B) may be used alone or in combination of two or more kinds. Furthermore, the bonding paste of the present invention may contain metal particles other than the metal particles (B) as long as the effects of the present invention are not impaired.

[0025] <Dispersion medium (C)> The bonding paste of the present invention contains a dispersion medium (C). The dispersion medium (C) disperses the metal particles (B), ensures the smoothness / leveling of the bonding film after application, and promotes densification of the bonding coating film.

[0026] Specific examples of the dispersion medium (C) include terpineol, dihydroterpineol, carbitol, carbitol acetate, butyl carbitol, isophorone, γ-butyl lactone, dipropylene glycol monomethyl ether, dipropylene glycol methyl-n-propyl ether, 3-methoxy-3-methylbutyl acetate, ethylene glycol, hexanoic acid, propylene glycol diacetate, dipropylene glycol methyl ether acetate, 1,3-butylene glycol, and isoparaffin-based solvents contained in hydrocarbon solvents. Among these, at least one selected from the group consisting of terpineol, dihydroterpineol, carbitol, carbitol acetate, butyl carbitol, isophorone, γ-butyrolactone, and dipropylene glycol monomethyl ether is preferred. These dispersion media (C) may be used alone or in combination of two or more.

[0027] <Polyamide (A)> The joining paste of the present invention contains a polyamide (A) which is a polymer of a polybasic acid monomer and a polyamine monomer and has a phenolic hydroxyl group in its side chain (hereinafter referred to as "phenolic hydroxyl group-containing polyamide (A)"). Moreover, the polyamide (A) satisfies the following (i) and / or (ii): (i) The polyamide (A) is a polyamide (A-1) in which the phenolic hydroxyl group and the hydrocarbon group having 20 to 60 carbon atoms (but excluding the aromatic ring to which the phenolic hydroxyl group is bonded) are contained within the same polymer. (ii) The polyamide (A) is a polyamide (A-3) which is a mixture of a polyamide (a-1) having a phenolic hydroxyl group in the side chain and a polyamide (a-2) having a hydrocarbon group having 20 to 60 carbon atoms. By combining the specific polyamide of the present application having such a phenolic hydroxyl group and a hydrocarbon group having 20 to 60 carbon atoms with the above-mentioned metal particles (B), the resulting bonding paste exhibits excellent coating properties. In addition, the generation of voids in the bonding coating film is suppressed, and a dense coating film is formed. As a result, it is possible to achieve both excellent bonding strength and cycle characteristics.

[0028] The method for synthesizing the polyamide (A) is not limited, but it is usually synthesized using a polybasic acid compound selected from dibasic or higher polybasic acids, and their acid anhydrides or lower alkyl esters, and a dibasic or higher polyamine compound. The phenolic hydroxyl group-containing polyamide (A) used in the present invention may have a terminal carboxy group or an amino group, or may not have a functional group at the terminal.

[0029] In the present invention, the hydrocarbon group having 20 to 60 carbon atoms refers to a hydrocarbon group having 20 to 60 carbon atoms contained in all or part of a residue other than a functional group that contributes to the polymerization of a monomer, and the number of carbon atoms is the number of carbon atoms in a continuous structure that does not contain elements other than carbon and hydrogen. As the hydrocarbon group having 20 to 60 carbon atoms, preferably, all of the residues other than the functional groups that contribute to the polymerization of the monomer are hydrocarbon groups having 20 to 60 carbon atoms. That is, the carbon number refers to the total number of carbon atoms in the continuous hydrocarbon groups, including the main chain and the side chains directly connected to the main chain of the polyamide, and includes aliphatic hydrocarbon groups (having alicyclic hydrocarbon groups) as well as aromatic hydrocarbon groups. However, aromatic rings to which phenolic hydroxyl groups are bonded are not included in the carbon number. On the other hand, carbon atoms in the hydrocarbon groups bonded via aromatic rings to which phenolic hydroxyl groups are bonded are each counted as a separate hydrocarbon group.

[0030] Moreover, the polyamide (A) more preferably satisfies the following (iii) to (v). (iii) The monomers constituting the polyamide (A-1) include a monomer having a phenolic hydroxyl group and a monomer having a hydrocarbon group having 20 to 60 carbon atoms. (iv) The polybasic acid monomer and / or the polyamine monomer constituting the polyamide (a-1) contain a monomer having a phenolic hydroxyl group, and the polybasic acid monomer and the polyamine monomer do not contain a monomer having a hydrocarbon group having 20 to 60 carbon atoms. (v) The polybasic acid monomer and / or the polyamine monomer constituting the polyamide (a-2) contain a monomer having a hydrocarbon group having 20 to 60 carbon atoms, and the polybasic acid monomer and the polyamine monomer do not contain a monomer having a phenolic hydroxyl group.

[0031] More preferably, the polyamide (A) further satisfies the following (vi): (vi) At least a part of the monomers having a hydrocarbon group with 20 to 60 carbon atoms includes a compound having a cyclic structure with 5 to 10 carbon atoms.

[0032] In (iii), it goes without saying that a monomer having a phenolic hydroxyl group and a hydrocarbon group having 20 to 60 carbon atoms may be used within the same monomer. In addition, in (vi), "including a compound having a cyclic structure having 5 to 10 carbon atoms" means that at least a part of the monomers having a hydrocarbon group having 20 to 60 carbon atoms contains a monomer having a cyclic structure having 5 to 10 carbon atoms.

[0033] The carbon number of the monomer having a hydrocarbon group having 20 to 60 carbon atoms is preferably 24 to 56, more preferably 28 to 48, and even more preferably 36 to 44, from the viewpoint of effectively bringing out solubility and flexibility.

[0034] From the viewpoints of solubility in general-purpose solvents, productivity, and initial bonding strength, the polyamide (A) is preferably the polyamide (A-1).

[0035] <Polyamide (A-1)> A preferred embodiment of the polyamide (A-1) is obtained by polymerizing a polybasic acid monomer (m1) and a polyamine monomer (m2), has a phenolic hydroxyl group in a side chain, and has a phenolic hydroxyl group and a C20-60 hydrocarbon group in the same polymer. The polyamide (A-1) only needs to satisfy the above conditions, and polybasic acid monomers and polyamine monomers having other structures can be appropriately used within the scope of the present invention. That is, the polybasic acid monomer (m1) is selected from at least one selected from the group consisting of polybasic acid compounds having a phenolic hydroxyl group, polybasic acid compounds having a C20-60 hydrocarbon group, and other polybasic acid compounds, and the polyamine monomer (m2) is selected from at least one selected from the group consisting of polyamine compounds having a phenolic hydroxyl group, polyamine compounds having a C20-60 hydrocarbon group, and other polyamine compounds, so that the polymer contains a phenolic hydroxyl group and a C20-60 hydrocarbon group. The compound having a C20-60 hydrocarbon group and the compound having a phenolic hydroxyl group can be polymerized by selecting a polybasic acid monomer (m1) and the polyamine monomer (m2) so that they are contained in the same type of monomer or in different monomers, to obtain a phenolic hydroxyl group-containing polyamide (A-1).

[0036] The above "so as to be included in the same type of monomer" means that a polybasic acid compound having a phenolic hydroxyl group and a polybasic acid compound having a C20-60 hydrocarbon group may be used as the polybasic acid monomer (m1), or a polyamine compound having a phenolic hydroxyl group and a polyamine compound having a C20-60 hydrocarbon group may be used as the polyamine monomer (m2). Also, "so as to be included in another monomer" means that a polybasic acid compound having a phenolic hydroxyl group may be included as the polybasic acid monomer (m1) and a polyamine compound having a C20-60 hydrocarbon group may be included as the polyamine monomer (m2), or a polybasic acid compound having a C20-60 hydrocarbon group may be included as the polyamine monomer (m1) and a polyamine compound having a phenolic hydroxyl group may be included as the polyamine monomer (m2). In either case, other polybasic acid compounds and other polyamine compounds may be used as appropriate.

[0037] When a dibasic acid monomer and a diamine monomer are used as the monomers, the resulting polyamide (A) has a structural unit represented by the following general formula (1). [ka]

[0038] In the general formula (1), R1 is a divalent linking group which is a polybasic acid compound residue which may have an independent structure for each structural unit, R2 is a divalent linking group which is a polyamine compound residue which may have an independent structure for each structural unit, at least one of R1 and R2 contains a linking group having a phenolic hydroxyl group, and at least one of R1 and R2 has a linking group having a C20-60 hydrocarbon group. The polyamide (A-1) is a compound in which at least two structural units represented by -CO-R1-CO-NH-R2-NH- are repeated. Within the scope of the present invention, a compound having one structural unit of general formula (1) and having a blocked end may be contained in the thermosetting resin composition.

[0039] The monomer having a phenolic hydroxyl group and the monomer having a C20-60 hydrocarbon group may be contained in at least one of the dibasic acid compound and the diamine compound, and these groups may be contained in both the dibasic acid compound and the diamine compound.

[0040] <Polybasic acid monomer (m1)> [Polybasic acid compounds having phenolic hydroxyl groups] The polybasic acid compound having a phenolic hydroxyl group is not particularly limited, and examples thereof include hydroxyisophthalic acids such as 2-hydroxyisophthalic acid, 4-hydroxyisophthalic acid, and 5-hydroxyisophthalic acid, dihydroxyisophthalic acids such as 2,5-dihydroxyisophthalic acid, 2,4-dihydroxyisophthalic acid, and 4,6-dihydroxyisophthalic acid, dihydroxyterephthalic acids such as 2-hydroxyterephthalic acid, 2,3-dihydroxyterephthalic acid, and 2,6-dihydroxyterephthalic acid, hydroxyphthalic acids such as 4-hydroxyphthalic acid and 3-hydroxyphthalic acid, and dihydroxyphthalic acids such as 3,4-dihydroxyphthalic acid, 3,5-dihydroxyphthalic acid, 4,5-dihydroxyphthalic acid, and 3,6-dihydroxyphthalic acid. In addition, acid anhydrides of these acids and ester derivatives such as polybasic acid methyl esters may also be used. The only difference is that in the case of free polybasic acids and acid anhydrides, a dehydration reaction occurs, while in the case of ester derivatives, a corresponding dealcoholization reaction occurs. Among these, 5-hydroxyisophthalic acid is preferred from the viewpoints of copolymerizability, availability, etc. When 5-hydroxyisophthalic acid is used, R1 in general formula (1), i.e., the divalent linking group which is a polybasic acid compound residue, is a moiety obtained by removing two carboxy groups from the 5-hydroxyisophthalic acid.

[0041] [Polybasic acid compounds with C20-60 hydrocarbon groups] Suitable examples of polybasic acid compounds having a C20-60 hydrocarbon group include polybasic acid compounds having a cyclic structure and 5-10 carbon atoms, which are obtained by reacting a monobasic unsaturated fatty acid having 10-24 carbon atoms and one or more double bonds or triple bonds. Suitable examples of such polybasic acid compounds include natural fatty acids such as soybean oil fatty acids, tall oil fatty acids, and rapeseed oil fatty acids, and polybasic acid compounds containing dimerized fatty acids (dimer acids) obtained by subjecting these to a Diels-Alder reaction using refined oleic acid, linoleic acid, linolenic acid, erucic acid, and the like.

[0042] The number of cyclic structures may be one or two, and in the case of two, the two rings may be independent or may be continuous. Examples of the cyclic structure include a saturated alicyclic structure, an unsaturated alicyclic structure, and an aromatic ring. The carboxy group may be directly bonded to the cyclic structure, but from the viewpoint of improving solubility and flexibility, the carboxy group is preferably bonded to the cyclic structure via an aliphatic chain. The number of carbon atoms between the carboxy group and the cyclic structure is preferably 2 to 25. In addition, from the viewpoints of improving solubility, improving flexibility, and decreasing the dielectric constant and dielectric tangent, the polybasic acid compound having a C20-60 hydrocarbon group preferably has a chain-like alkyl group having high freedom and hydrophobicity as a portion other than the cyclic structure. Preferably, there are two or more alkyl groups per cyclic structure. The number of carbon atoms in the alkyl group is preferably 2 to 25.

[0043] Polybasic acid compounds having C20-60 hydrocarbon groups are generally obtained as compositions mainly composed of monomers containing a dimer derived from a dimer acid as a residue, and also containing fatty acids as raw materials and fatty acids of trimerization or higher. In particular, it is preferable that 100% by mass of polybasic acid compounds having C20-60 hydrocarbon groups contain preferably 70% by mass or more, more preferably 95% by mass or more, of monomers containing a dimer derived from a dimer acid as a residue. Also, dimers with a lower degree of unsaturation obtained by hydrogenating them (hydrogenation reaction) are preferably used from the viewpoints of oxidation resistance (particularly coloring at high temperatures) and suppression of gelation during synthesis. As the polybasic acid compound having a C20-60 hydrocarbon group, it is preferable to use a polybasic acid compound containing a dimer derived from a monobasic unsaturated fatty acid having 10-24 carbon atoms as a residue. Furthermore, it is preferable to use a monomer containing a trimer, which is a tricarboxylic acid, as a residue, derived from a monobasic unsaturated fatty acid having 10-24 carbon atoms as a part of the polybasic acid compound having a C20-60 hydrocarbon group.

[0044] Examples of commercially available polybasic acid compounds having a C20-60 hydrocarbon group include "Pripol 1004", "Pripol 1006", "Pripol 1009", "Pripol 1013", "Pripol 1015", "Pripol 1017", "Pripol 1022", "Pripol 1025", and "Pripol 1040" manufactured by Croda Japan Ltd.; and "Empol 1008", "Empol 1012", "Empol 1016", "Empol 1026", "Empol 1028", "Empol 1043", "Empol 1061", and "Empol 1062" manufactured by BASF Japan Ltd. These polybasic acid compounds can be used alone or in combination.

[0045] [Other polybasic acid compounds] The polybasic acid compounds other than the polybasic acid compounds having a phenolic hydroxyl group and the polybasic acid compounds having a C20-60 hydrocarbon group are not particularly limited within the scope of the present invention. Examples of such other polybasic acid compounds include dibasic acid compounds and polybasic acid compounds having three or more functional groups. Examples of the dibasic acid compound include aromatic dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, 1,4-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, benzophenone-4,4'-dicarboxylic acid, and 4,4'-biphenyldicarboxylic acid; aliphatic dibasic acids such as oxalic acid, malonic acid, methylmalonic acid, succinic acid, glutaric acid, adipic acid, maleic acid, fumaric acid, malic acid, tartaric acid, thiomalic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, hexadecanedioic acid, and diglycolic acid; and alicyclic dibasic acids such as 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, and 1,3-cyclopentanedicarboxylic acid. Examples of trifunctional or higher polybasic acid compounds include trimellitic acid, hydrogenated trimellitic acid, pyromellitic acid, hydrogenated pyromellitic acid, and 1,4,5,8-naphthalenetetracarboxylic acid.

[0046] The other polybasic acid compounds may be used alone or in combination. Among them, isophthalic acid and 1,4-cyclohexanedicarboxylic acid are preferably used because they can provide a stronger polyamide with better heat resistance. In addition, by using a compound having three or more functional groups, a branched structure can be introduced into the polyamide, which can increase the molecular weight and increase the cohesive strength of the resulting polyamide. As a result, the heat resistance can be improved without adversely affecting the adhesiveness.

[0047] Furthermore, in the present invention, a monofunctional monobasic acid compound can be used in combination. By using a monofunctional compound, the number of carboxyl groups and amino groups that can become terminal functional groups of the polyamide can be reduced, and the molecular weight of the resulting polyamide can be controlled. As a result, the stability over time of the polyamide resin can be improved. Examples of the monobasic acid compound include benzoic acid, 4-hydroxybenzoic acid, and 2-ethylhexanoic acid.

[0048] <Polyamine monomer (m2)> The polyamine compound having a phenolic hydroxyl group is not particularly limited, but examples thereof include polyamines represented by the following general formula (2).

[0049] [ka]

[0050] In the formula, R3 represents a direct bond or a group consisting of carbon, hydrogen, oxygen, nitrogen, sulfur, or halogen, and examples thereof include a divalent hydrocarbon group having 1 to 30 carbon atoms, a divalent hydrocarbon group having 1 to 30 carbon atoms in which some or all of the hydrogen atoms have been substituted with halogen atoms, -(C=O)-, -SO2-, -O-, -S-, -NH-(C=O)-, -(C=O)-O-, a group represented by the following general formula (3), and a group represented by the following general formula (4). In the formula, r and s each independently represent an integer of 1 to 20, and R4 represents a hydrogen atom or a methyl group.

[0051] [ka]

[0052] [ka]

[0053] The above R3 is preferably a direct bond.

[0054] In addition, when a compound of general formula (2) is used, R2 in general formula (1), i.e., a divalent linking group which is a polyamine compound residue, is the portion obtained by removing two amino groups from the compound of general formula (2).

[0055] [Polyamine compounds having C20-60 hydrocarbon groups] Examples of polyamine compounds having a C20-60 hydrocarbon group include compounds obtained by converting the carboxy group of the polybasic acid compound having a C20-60 hydrocarbon group into an amino group. Commercially available products of such polyamine compounds include "Priamine 1071", "Priamine 1073", "Priamine 1074", and "Priamine 1075" manufactured by Croda Japan Ltd. and "Versamine 551" manufactured by BASF Japan Ltd. These polyamine compounds can be used alone or in combination. Among them, "Priamine 1071" containing about 20 to 25% by mass of a triamine component which is a trimer is preferable because it improves the cohesive force of the polyamide and improves the heat resistance. From the viewpoint of the production stability of the polyamide, the total amount of the triamine which is a trimer and the tricarboxylic acid which is a trimer is preferably 0.1 to 20% by mass, more preferably 1 to 10% by mass, of 100% by mass of all monomers used to form the polyamide.

[0056] [Other polyamine compounds] The polyamine compounds other than the polyamine compounds having a phenolic hydroxyl group and the polyamine compounds having a C20-60 hydrocarbon group are not particularly limited within the scope of the present invention. Examples of such other polyamine compounds include trifunctional or higher polyamine compounds such as diamine compounds and triamine compounds. Examples of the diamine compound include 1,4-diaminobenzene, 1,3-diaminobenzene, 1,2-diaminobenzene, 1,5-diaminonaphthalene, 1,8-diaminonaphthalene, 2,3-diaminonaphthalene, 2,6-diaminotoluene, 2,4-diaminotoluene, 3,4-diaminotoluene, 4,4'-diaminodiphenylmethane, 3,4'-diaminodiphenylether, 4,4'-diaminodiphenylether, 4,4'-diamino-1,2-diphenylethane, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diaminobenzophenone, 4,4'-diamino aromatic diamines such as 3,3'-diaminodiphenylsulfone, 3,3'-diaminobenzophenone, and 3,3'-diaminodiphenylsulfone; aliphatic diamines such as ethylenediamine, 1,3-propanediamine, 1,4-butanediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,9-nonanediamine, 1,12-dodecamethylenediamine, and metaxylenediamine; and alicyclic diamines such as isophoronediamine, norbornanediamine, 1,2-cyclohexanediamine, 1,3-cyclohexanediamine, 1,4-cyclohexanediamine, 4,4'-diaminodicyclohexylmethane, and piperazine. Examples of trifunctional or higher polyamine compounds include 1,2,4-triaminobenzene and 3,4,4'-triaminodiphenyl ether. In addition, compounds that have an aromatic ring but no directly bonded amino group are classified as aliphatic.

[0057] The other polyamine compounds may be used alone or in combination. Among them, isophorone diamine and norbornane diamine are preferably used because they can provide a tough polyamide having excellent heat resistance. In addition, by using a trifunctional or higher functional group, a branched structure can be introduced into the polyamide, which can increase the molecular weight and the cohesive strength of the resulting polyamide, thereby improving the adhesiveness, heat resistance, etc.

[0058] Furthermore, in the present invention, a monofunctional amine compound can be used in combination. By using a monofunctional compound, the number of carboxyl groups and amino groups that can become terminal functional groups of the polyamide can be reduced, and the molecular weight of the resulting polyamide can be controlled. As a result, the stability over time of the polyamide resin can be improved. Examples of the monofunctional amine compound include aniline, 4-aminophenol, and 2-ethylhexylamine.

[0059] The phenolic hydroxyl group-containing polyamide (A-1) of the present invention can be obtained by appropriately selecting the polybasic monomer (m1) and polyamine monomer (m2) according to the properties to be improved, such as adhesion and heat resistance.

[0060] The polyamide (A-1) obtained by polymerization may be a random polymer or a block polymer of a component having a phenolic hydroxyl group and a component having a C20-60 hydrocarbon group. That is, it may be a polymer of a mixture of a plurality of polybasic acid monomer compounds and one polyamine compound, a polymer of a mixture of a plurality of polybasic acid compounds and a mixture of a plurality of polyamine compounds, a polymer of a mixture of a single polybasic acid compound and a plurality of polyamine compounds, or a polymer of a single polybasic acid compound and a single polyamine compound. The polymer may be one in which other polybasic acid compounds or other polyamine compounds are further polymerized depending on the functional groups remaining at the terminals.

[0061] The polyamide (A-1) of the present invention preferably contains 10 to 95 mol %, more preferably 14 to 92 mol %, and even more preferably 18 to 88 mol % of a compound having a C20 to 60 hydrocarbon group out of a total of 100 mol of all monomers used in the synthesis of the polyamide, i.e., the polybasic acid monomer (m1), the polyamine monomer (m2), and the monobasic acid or monofunctional amine compound used as needed.

[0062] The method for calculating the number of moles of a monomer having a C20-60 hydrocarbon group will be described. First, the molecular weight (M) of a monomer having a C20-60 hydrocarbon group is calculated by the following formula. M = (56.11 × F × 1000) / E F: Number of functional groups of monomers having C20-60 hydrocarbon groups E: Acid value of monomers with C20-60 hydrocarbon groups (mgKOH / g) Next, the mass of the compound having a C20-60 hydrocarbon group used in the polymerization is divided by the molecular weight (M) to determine the number of moles of the compound having a C20-60 hydrocarbon group used in the polymerization. Similarly, the number of moles of each monomer used in the polymerization is determined, and these are summed to determine the number of moles of all monomers used in the polymerization. Then, the proportion (mol%) of the compound having a C20-60 hydrocarbon group can be determined by dividing the number of moles of the compound having a C20-60 hydrocarbon group by the number of moles of all monomers.

[0063] <Polyamide (A-3)> The polyamide (A-3) is a polyamide obtained by mixing a polyamide (a-1) having a phenolic hydroxyl group in the side chain and (a-2) having a hydrocarbon group having 20 to 60 carbon atoms. One of the preferred aspects of the polyamide (a-1) is a polyamide obtained by polymerizing a polybasic acid monomer (m3) and a polyamine monomer (m4), has a phenolic hydroxyl group in a side chain, and does not have a C20-60 hydrocarbon group. The polyamide (a-1) only needs to satisfy the above conditions, and other polybasic acid monomers and polyamine monomers can be used appropriately. That is, the polybasic acid monomer (m3) is at least one selected from the group consisting of a polybasic acid compound having a phenolic hydroxyl group and other polybasic acid compounds (excluding polybasic acid compounds having a C20-60 hydrocarbon group), and the polyamine monomer (m4) is at least one selected from the group consisting of a polyamine compound having a phenolic hydroxyl group and other polyamine compounds (excluding polyamine compounds having a C20-60 hydrocarbon group), and at least one of the polybasic acid monomer (m3) and the polyamine monomer (m4) has a phenolic hydroxyl group. The polyamide (a-1) may be prepared by combining a divalent monomer with a trivalent or higher monomer to introduce a branched structure and adjust the molecular weight appropriately. It is also possible to maintain the molecular weight appropriately by using a monovalent monomer.

[0064] One of the preferred embodiments of the polyamide (a-2) is obtained by polymerizing a polybasic acid monomer (m5) and a polyamine monomer (m6), and has a C20-60 hydrocarbon group but does not have a phenolic hydroxyl group in the side chain. The polybasic acid monomer (m5) is at least one selected from the group consisting of polybasic acid compounds having a C20-60 hydrocarbon group and other polybasic acid compounds (however, polybasic acid compounds having a phenolic hydroxyl group are excluded), and the polyamine monomer (m6) is at least one selected from the group consisting of polyamine compounds having a C20-60 hydrocarbon group and other polyamine compounds (however, polyamine compounds having a phenolic hydroxyl group are excluded), and at least one of the polybasic acid monomer (m5) and the polyamine monomer (m6) has a C20-60 hydrocarbon group.

[0065] In other words, polyamide (A-3) is a mixture of polyamide (a-1) having a phenolic hydroxyl group in the side chain but no C20-60 hydrocarbon group, and polyamide (a-2) having a C20-60 hydrocarbon group but no phenolic hydroxyl group in the side chain. The mixing ratio of polyamide (a-1) to polyamide (a-2) can be appropriately adjusted depending on the phenolic hydroxyl value and molecular weight of (a-1). However, the polyamide (a-1):polyamide (a-2) ratio is preferably 5:95 to 80:20 (mass ratio), and more preferably 10:90 to 50:50.

[0066] The polybasic acid monomer (m3) may be any of the above-mentioned polybasic acid monomers (m1) other than polybasic acid compounds having a C20 to 60 hydrocarbon group. A monobasic compound may also be used in combination. The polyamine monomer (m4) may be any of the above-mentioned polyamine monomers (m2) other than the polyamine compounds having a C20 to 60 hydrocarbon group. A monofunctional amine compound may also be used in combination.

[0067] The polybasic acid monomer (m5) may be any of the above-mentioned polybasic acid monomers (m1) other than the polybasic acid compounds having a phenolic hydroxyl group. A monobasic compound may also be used in combination. The polyamine monomer (m6) may be any of the above-mentioned polyamine monomers (m2) other than the polyamine compound having a phenolic hydroxyl group. A monofunctional amine compound may also be used in combination.

[0068] The polyamide (A-3) of the present invention preferably contains 10 to 95 mol %, more preferably 14 to 92 mol %, and even more preferably 18 to 88 mol %, of a compound having a C20 to C60 hydrocarbon group, based on a total of 100 mol of all the monomers (m3) to (m6) used in the formation thereof and the monobasic acid and monofunctional amine compound used as necessary.

[0069] [Phenol hydroxyl value] The amount of phenolic hydroxyl groups in the polyamide (A) can be adjusted depending on the purpose, but is preferably 1 to 80 mgKOH / g, more preferably 5 to 60 mgKOH / g, and even more preferably 5 to 30 mgKOH / g. When the phenolic hydroxyl value is 1 mgKOH / g or more, a dense crosslinked structure can be formed, and the resistance, hardness, and heat resistance of the cured coating film can be improved. When the phenolic hydroxyl value is 80 mgKOH / g or less, a cured coating film with good adhesion and flexibility can be obtained. When the phenolic hydroxyl value is within the range of 1 to 80 mgKOH / g, the adhesion, flexibility, and heat resistance of the resulting coating film are improved, which is preferable.

[0070] The phenolic hydroxyl value can be adjusted by the blending composition of monomers having a phenolic hydroxyl group among all the monomers constituting the polyamide (A-1), or the polyamide (a-1) and the polyamide (a-2). For example, in the case of polyamide (A) obtained by reacting only 5-hydroxyisophthalic acid having a phenolic hydroxyl group as the polybasic acid compound and only dimer diamine having a C20 to C60 hydrocarbon group and no phenolic hydroxyl group as the polyamine compound, the phenolic hydroxyl value is close to 80 mgKOH / g, and the heat resistance of the thermoset product is further improved.

[0071] When the polyamide (A) is polyamide (A-3), its phenolic hydroxyl value is the phenolic hydroxyl value of a mixture of polyamide (a-1) and polyamide (a-2).

[0072] [Mass average molecular weight] The mass average molecular weight of the polyamide (A-1) is preferably from 3,000 to 1,000,000, more preferably from 5,000 to 550,000, and even more preferably from 10,000 to 300,000, from the viewpoints of handleability and dispersibility of metal particles through interaction with the metal particles. The mass average molecular weight of the polyamide (a-1) is preferably from 500 to 30,000, more preferably from 1,000 to 20,000, and even more preferably from 1,000 to 10,000, from the viewpoint of solubility in general-purpose solvents described below. The weight average molecular weight of the polyamide (a-2) is preferably in the same range as that of the polyamide (A-1).

[0073] [Glass transition temperature] The glass transition temperature of the polyamide (A) is preferably −40° C. to 120° C., and more preferably −30° C. to 80° C. By setting the glass transition temperature of the polyamide (A) in the range of −40° C. to 120° C., it is possible to suppress extrusion during bonding, and further to achieve good embedding properties in the substrate, thereby further improving the adhesiveness.

[0074] The glass transition temperature can be adjusted by the blending ratio of the monomer having a C20-60 hydrocarbon group. For example, by increasing the blending ratio of the monomer having a C20-60 hydrocarbon group, the concentration of amide bonds with high water absorption decreases, and the flexibility characteristic of dimerized fatty acid is imparted, so that the glass transition temperature becomes close to -40°C.

[0075] When the polyamide (A) is polyamide (A-3), its glass transition temperature is the glass transition temperature of a mixture of polyamide (a-1) and polyamide (a-2).

[0076] <Synthesis of polyamide (A)> The polymerization method of the polyamide (A) used in the present invention is not particularly limited, and known methods such as melt polymerization, interfacial polymerization, solution polymerization, bulk polymerization, solid-phase polymerization, and combinations of these methods can be used. Industrially, the reaction is generally carried out at 150 to 300°C for about 1 to 24 hours in the presence or absence of a catalyst, and it is preferable to carry out the reaction at 180 to 270°C under reduced pressure below atmospheric pressure in order to promote the dehydration or dealcoholization reaction and to avoid coloration and decomposition reactions due to high temperatures.

[0077] Examples of the catalyst that can be used in the polymerization include inorganic phosphorus compounds such as phosphoric acid, phosphorous acid, hypophosphorous acid, pyrophosphoric acid, polyphosphoric acid, and alkali metal salts and alkaline earth metal salts thereof; phosphites such as triphenyl phosphite and diphenyl phosphite; titanium-based catalysts such as tetrabutyl orthotitanate and tetraisopropyl orthotitanate; tin-based catalysts such as dibutyltin oxide, dibutyltin laurate and monobutylhydroxytin oxide; and zirconium-based catalysts such as tetrabutoxyzirconium, zirconium acetate and zirconium octylate. These catalysts may be used in combination of two or more kinds.

[0078] <Joining paste> The bonding paste of the present invention can be produced by uniformly mixing and dispersing the above-mentioned polyamide (A), metal particles (B), and dispersion medium (C) by a conventionally known method. The method for mixing and dispersing the bonding paste is not particularly limited, and for example, a disperser, a three-roll mill, a bead mill, an ultrasonic disperser, or a self-revolving stirrer dispenser can be used.

[0079] The bonding paste of the present invention preferably contains polyamide (A) in the range of 0.01 to 1.70% by mass based on the mass of the metal particles (B). When the content of polyamide (A) is 0.01% by mass or more, the fluidity of the paste is improved and the bonding coating film is densified. This suppresses the generation of voids during heating during bonding, and allows the development of good bonding strength and thermal cycle characteristics. When the content is 1.70% by mass or less, the amount of organic matter that causes voids in the bonding coating film is suppressed. This suppresses the generation of voids during heating during bonding, and allows the development of good bonding strength and thermal cycle characteristics. The content of polyamide (A) is more preferably 0.02% by mass or more, further preferably 0.04% by mass or more, particularly preferably 0.10% by mass or more. The content of polyamide (A) is more preferably 1.30% by mass or less, further preferably 1.00% by mass or less, particularly preferably 0.50% by mass or less.

[0080] In addition, the bonding paste of the present invention preferably has a ratio of metal particles (B) / dispersion medium (C) in the range of 80 / 20 to 98 / 2 (mass ratio), more preferably in the range of 85 / 15 to 96 / 4 (mass ratio), and even more preferably in the range of 90 / 10 to 94 / 6 (mass ratio). By being in the above range, it is possible to ensure good application suitability as a bonding paste, suppress the residue of organic components in the dried coating film, suppress the generation of voids during heating during bonding, and exhibit good bonding strength.

[0081] <Other ingredients> The bonding paste of the present invention may contain known components such as a curing agent, a sintering accelerator, a binder resin (excluding polyamide (A)), a dispersant, and additives, within the range that does not impair the effects of the present invention.

[0082] [Hardening agent] The curing agent that may be used in the present invention may be, for example, a compound having a functional group capable of reacting with the phenolic hydroxyl group of the polyamide (A). Examples of such compounds include an epoxy group-containing compound, an isocyanate group-containing compound, a carbodiimide group-containing compound, a metal chelate compound, a metal alkoxide, and a metal acylate. Furthermore, when the polyamide resin (A) has a carboxy group or an amino group as a terminal functional group, the polyamide resin (A) contains a mixture of functional groups such as a phenolic hydroxyl group, a carboxy group, and / or an amino group, and by selecting the above-mentioned curing agent, the processability and adhesion can be adjusted by utilizing the difference in reactivity with each functional group.

[0083] <zygote> The bonding paste of the present invention can bond a first body to a second body to obtain a bonded body. The method of applying the bonding paste to the body to be bonded is not particularly limited as long as it can apply the paste uniformly to the member, and examples of the method include various printing methods such as screen printing, flexographic printing, offset printing, gravure printing, metal mask printing, gravure offset printing, and dispenser coating. The thickness of the bonding coating is not limited, but is usually 3 μm to 500 μm, preferably 10 μm to 200 μm, and more preferably 20 μm to 100 μm.

[0084] The sintering conditions in the bonding step can be appropriately selected, and examples of the conditions include atmospheric pressure, a nitrogen atmosphere, a vacuum, pressurized, and a reducing atmosphere at 200 to 300° C. Examples of the sintering device include a hot air oven, an infrared oven, a reflow oven, a microwave oven, a hot plate, and a light sintering device. One of these devices may be used alone, or a plurality of devices may be used in combination. Prior to the firing step, a pre-drying step may be appropriately performed in order to remove organic components from the bonding coating film. For example, the pre-drying step may be performed by heating at a temperature in the range of 60 to 220°C and drying under reduced pressure using an apparatus similar to the above firing apparatus.

[0085] In addition, when placing the second object to be joined on the first object to be joined coated with the bonding paste of the present invention, the second object to be joined can be placed while applying pressure. The pressure is appropriately set depending on the viscosity of the bonding paste and the drying state of the paste, and is preferably 0.1 to 40 MPa, more preferably 0.3 to 30 MPa.

[0086] A preferred method for joining two objects to be joined includes applying the joining paste of the present invention to a first object to be joined, placing a second object to be joined on the applied surface, and heating the paste to about 200 to 300° C. at a heating rate of about 1° C. / min to 15° C. / min to perform sintering. After the temperature rise is completed, it is preferable to maintain the temperature higher than the temperature at the end of the temperature rise for about 10 minutes to 2 hours.

[0087] The type of the object to be joined is not particularly limited, and examples thereof include metal members, electronic elements, plastic materials, and ceramic materials. It is preferable to join metal members together, a metal member and a semiconductor element, or a metal member and an LED element.

[0088] Examples of the metal member include a copper substrate, a gold substrate, an aluminum substrate, etc. Examples of the electronic element include a semiconductor element, an LED element, and a power device element. Semiconductor elements include silicon and germanium, as well as gallium arsenide, gallium phosphide, cadmium sulfide, etc. LED elements include aluminum, silicon nitride, diamond, graphite, yttrium oxide, magnesium oxide, etc. In particular, it is possible to use power device elements of silicon carbide, gallium nitride, etc. Examples of plastic materials include polyimide, polyethylene, polypropylene, polyethylene terephthalate, polycarbonate, polyethylene naphthalate, etc. Examples of the ceramic material include glass and silicon. The first and second objects to be joined may be members of different kinds, not just the same kind. The members may be appropriately processed by corona treatment, plating, or the like in order to increase the joining strength. Examples of the metal member include a copper substrate, a gold substrate, and an aluminum substrate. Examples of electronic elements include semiconductor elements and LED elements. Examples of semiconductor elements include silicon, germanium, gallium arsenide, gallium phosphide, and cadmium sulfide. Examples of LED elements include aluminum, silicon nitride, diamond, graphite, yttrium oxide, and magnesium oxide. In particular, power device elements such as silicon carbide and gallium nitride can be used. Examples of plastic materials include polyimide, polyethylene, polypropylene, polyethylene terephthalate, polycarbonate, and polyethylene naphthalate. Examples of ceramic materials include glass and silicon.

[0089] The first and second objects to be joined may be members of different kinds, not just the same kind. The members may be subjected to a corona treatment or a plating treatment in order to increase the joining strength. EXAMPLES

[0090] The present invention will be described in detail below using examples and comparative examples, but the technical scope of the present invention is not limited thereto. In the examples, "parts" means "parts by mass" and "%" means "% by mass" unless otherwise specified. In addition, the numerical values ​​in the tables mean "parts" unless otherwise specified.

[0091] [Particle size measurement] Isopropyl alcohol was added to the metal particles, and the mixture was dispersed using an ultrasonic disperser to obtain a 0.5% by mass dispersion. The particle diameters of the metal particles in the dispersion were measured using Nanotrac UPA-EX150 (manufactured by Nikkiso Co., Ltd.) to determine d1, d50, and d99.

[0092] [Calculation of mass reduction rate] For each metal particle (B), a differential thermal-thermogravimetric simultaneous measurement device (TG-DTA, EXSTAR TG / DTA6200, manufactured by Seiko Instruments Inc.) was used to raise the temperature from 25° C. at a heating rate of 5° C. / min, and the mass reduction rate of the metal particle (B) at Te was determined when the mass of the metal particle (B) at Ts, Te, and Ts was taken as 100% by mass. As shown in FIG. 1, the extrapolated start temperature of the exothermic peak on the lowest temperature side shown in the DTA curve was taken as Ts, and the extrapolated end temperature of the exothermic peak on the highest temperature side shown in the DTA curve was taken as Te. Mass reduction rate = [(mass of metal particles (B) at Ts - mass of metal particles (B) at Te) / mass of metal particles (B) at Ts] x 100

[0093] <Production of metal particles> (Production example 1) Metal particles B1 Under a nitrogen atmosphere, 200 parts of toluene and 21.5 parts of silver hexanoate were mixed while stirring at 25°C, and 2.3 parts of diethylaminoethanol and 0.25 parts of oleic acid were added as dispersants to dissolve them. Then, 70.0 parts of a 20% aqueous solution of succinic acid dihydrazide (hereinafter referred to as SUDH) was added dropwise as a reducing agent, and the liquid color changed from light yellow to dark brown. The temperature was raised to 40°C to promote the reaction. After standing and separating, the aqueous phase was removed to remove excess reducing agent and impurities, and distilled water was added to the toluene layer several times, washing and separation were repeated, toluene was added, and the process of removing the supernatant after centrifugation was repeated twice. The precipitate was dried to obtain metal particles B1 in which silver particles were coated with hexanoic acid and oleic acid. The particle diameter of metal particles B1 was determined by the above-mentioned method, and d1 was 100 nm, d50 was 250 nm, and d99 was 450 nm.

[0094] (Production example 2) Metal particles B2 Except for changing the amount of diethylaminoethanol to 2.5 parts and the amount of oleic acid to 0.34 parts, metal particles B2 were obtained in the same manner as in Production Example 1. d1 was 35 nm, d50 was 110 nm, and d99 was 250 nm.

[0095] (Production example 3) Metal particles B3 Except for changing the amount of silver hexanoate to 23.5 parts and the amount of oleic acid to 0.18 parts, metal particles B3 were obtained in the same manner as in Production Example 1. d1 was 180 nm, d50 was 330 nm, and d99 was 600 nm.

[0096] (Production example 4) Metal particles B4 Except for using 21.5 parts of silver pentanoate instead of 21.5 parts of silver hexanoate and changing the amount of oleic acid to 0.3 parts, metal particles B4 were obtained in the same manner as in Production Example 1. d1 was 45 nm, d50 was 140 nm, and d99 was 300 nm.

[0097] (Production example 5) Metal particles B5 10 parts of silver nitrate were dissolved in 500 parts of ethylene glycol. Then, 5 parts of polyvinylpyrrolidone were dispersed in ethylene glycol. Then, ethylene glycol was heated to 150°C (reaction temperature), and the reaction was carried out for 1 hour while stirring at a rotation speed of 400 rpm while maintaining the reaction temperature at 150°C. At this time, the silver nitrate and ethylene glycol reacted with each other to generate nitrogen oxide gas, reduce the silver nitrate, and obtain a dispersion of metal particles coated with polyvinylpyrrolidone. The dispersion of metal particles was centrifuged, the supernatant was removed, ethylene glycol was added to the precipitate, and the mixture was stirred, then centrifuged again to remove the supernatant. The precipitate was dried to obtain metal particles B5 in which silver particles were coated with polyvinylpyrrolidone. d1 was 160 nm, d50 was 300 nm, and d99 was 650 nm.

[0098] (Production example 6) Metal particles B6 Except for using 32 parts of silver stearate instead of 21.5 parts of silver hexanoate and changing the amount of oleic acid to 0.28 parts, metal particles B6 were obtained in the same manner as in Production Example 1. d1 was 240 nm, d50 was 290 nm, and d99 was 420 nm.

[0099] (Production example 7) Metal particles B7 Except for using 18 parts of silver propionate instead of 21.5 parts of silver hexanoate and changing the amount of oleic acid to 0.29 parts, metal particles B7 were obtained in the same manner as in Production Example 1. d1 was 140 nm, d50 was 180 nm, and d99 was 250 nm.

[0100] (Production example 8) Metal particles B8 Except for using 33.5 parts of silver myristate instead of 21.5 parts of silver hexanoate and changing the amount of oleic acid to 0.28 parts, metal particles B8 were obtained in the same manner as in Production Example 1. d1 was 70 nm, d50 was 200 nm, and d99 was 750 nm.

[0101] (metal particle b1) As the metal particles b1, silver particles "LM1" manufactured by Tokusen Kogyo Co., Ltd. were used. d1 was 100 nm, d50 was 1000 nm, and d99 was 3200 nm.

[0102] (Production example 9) Metal particles b2 Metal particles b2 in which silver particles are coated with hexanoic acid and oleic acid were obtained in the same manner as in Production Example 1, except that the amount of diethylaminoethanol was changed to 1.5 parts and the amount of oleic acid was changed to 0.13 parts. d1 was 110 nm, d50 was 600 nm, and d99 was 1100 nm.

[0103] (Production example 10) Metal particles b3 6 parts of oleic acid, 140 parts of n-octylamine, 43 parts of N,N-dimethyl-1,3-diaminopropane, 16 parts of n-dodecylamine, 12 parts of cyclohexylamine, and 64 parts of n-butylamine were added and stirred for about 1 minute. Next, 320 parts of silver oxalate were added and stirred for about 10 minutes to obtain a composition for preparing silver particles. Then, the mixture was stirred for 30 minutes at 40°C, and further stirred for 30 minutes at 90°C. After cooling, 1500 parts of methanol was added and stirred, and then a centrifugation operation was performed for 1 minute in a centrifuge to remove the supernatant. The steps of adding 1500 parts of methanol, stirring, centrifugation, and removing the supernatant were repeated twice, and then dried to obtain metal particles b3 in which silver particles are coated with oxalic acid. d1 was 37 nm, d50 was 80 nm, and d99 was 165 nm.

[0104] (Production example 11) Metal particles b4 Metal particles b4 in which silver particles are coated with hexanoic acid and oleic acid were obtained in the same manner as in Production Example 1, except that the amount of silver hexanoate was changed from 21.5 parts to 23 parts and the amount of oleic acid was changed to 0.28 parts. d1 was 5 nm, d50 was 10 nm, and d99 was 27 nm.

[0105] <Synthesis of polyamide> (Synthesis Example 1) Polyamide (A-1-1) In a four-neck flask equipped with a stirrer, reflux condenser, nitrogen inlet tube, inlet tube, and thermometer, 202.9g (0.35mol in terms of dibasic acid) of Pripol 1009 as a polybasic acid compound having 36 carbon atoms, 25.7g (0.14mol) of 5-hydroxyisophthalic acid as a polybasic acid compound having a phenolic hydroxyl group, 35.1g (0.21mol) of terephthalic acid as other polybasic acid compounds, 313.9g of Priamine 1074 (0.59mol in terms of diamine) as a polyamine compound having 36 carbon atoms, and 100g of ion-exchanged water were charged and stirred until the temperature of the heat generation became constant. When the temperature stabilized, the temperature was raised to 110°C, and after confirming the outflow of water, the temperature was raised to 120°C after 30 minutes, and the dehydration reaction was continued while raising the temperature by 10°C every 30 minutes. When the temperature reached 230°C, the reaction was continued at that temperature for 3 hours, and then the mixture was kept under a vacuum of about 2 kPa for 1 hour, and the temperature was then lowered. Finally, an antioxidant and toluene were added to obtain a solution of a phenolic hydroxyl group-containing polyamide resin having a weight average molecular weight of 9,800, an acid value of 22.8 mgKOH / g, an amine value of 0.3 mgKOH / g, a phenolic hydroxyl value of 13.7 mgKOH / g, a glass transition temperature of 4°C, and a solid content of 40%. The monomers having C20-60 hydrocarbon groups accounted for 72.7 mol% of the total monomers used in the reaction (100 mol%).

[0106] (Synthesis Example 2) Polyamide (A-1-2) In a four-neck flask equipped with a stirrer, reflux condenser, nitrogen inlet tube, inlet tube, and thermometer, 51.4 g of 5-hydroxyisophthalic acid as a polybasic acid compound having a phenolic hydroxyl group, 70.3 g of isophthalic acid as another polybasic acid compound, 313.9 g of Priamine 1074 as a polyamine compound having 36 carbon atoms, and 100 g of ion-exchanged water were charged and stirred until the temperature of the heat generation became constant. When the temperature stabilized, the temperature was raised to 110°C, and after confirming the outflow of water, the temperature was raised to 120°C after 30 minutes, and then the dehydration reaction was continued while raising the temperature by 10°C every 30 minutes. When the temperature reached 230°C, the reaction was continued at that temperature for 3 hours, and then the temperature was lowered by holding it under a vacuum of about 2 kPa for 1 hour. Finally, an antioxidant and toluene were added to obtain a solution of a phenolic hydroxyl group-containing polyamide resin having a weight average molecular weight of 7,400, an acid value of 30.3 mgKOH / g, an amine value of 0.7 mgKOH / g, a phenolic hydroxyl value of 36.3 mgKOH / g, a glass transition temperature of 34°C, and a solid content of 40%. The monomer having a C20-60 hydrocarbon group was 45.5 mol% out of 100 mol% of all monomers used in the reaction.

[0107] (Synthesis Example 3) Polyamide (A-1-3) In a four-neck flask equipped with a stirrer, reflux condenser, nitrogen inlet tube, inlet tube, and thermometer, 405.7g of Pripol 1009 as a polybasic acid compound with 36 carbon atoms, 76.2g of 4,4'-diamino-3,3'-dihydroxybiphenyl as a polyamine compound having a phenolic hydroxyl group, 111.2g of Wondamin HM as another amine compound, and 100g of ion-exchanged water were charged and stirred until the temperature of the heat generation became constant. When the temperature stabilized, the temperature was raised to 110°C, and after confirming the outflow of water, the temperature was raised to 120°C after 30 minutes, and then the dehydration reaction was continued while raising the temperature by 10°C every 30 minutes. When the temperature reached 230°C, the reaction was continued at that temperature for 3 hours, and then the temperature was lowered by holding it under a vacuum of about 2kPa for 1 hour. Finally, an antioxidant and toluene were added to obtain a solution of a phenolic hydroxyl group-containing polyamide resin having a weight average molecular weight of 6,800, an acid value of 0.5 mgKOH / g, an amine value of 33.3 mgKOH / g, a phenolic hydroxyl value of 66.7 mgKOH / g, a glass transition temperature of 45°C, and a solid content of 40%. The monomer having a C20-60 hydrocarbon group was 44.4 mol% out of 100 mol% of all monomers used in the reaction.

[0108] (Synthesis Example 4) Polyamide (A-3-1) In a four-neck flask equipped with a stirrer, reflux condenser, nitrogen inlet tube, inlet tube, and thermometer, 48.6g (0.21mol) of dodecanedioic acid as other polybasic acid compounds, 6.9g (0.03mol) of 4,4'-diamino-3,3'-dihydroxybiphenyl as a polyamine compound having a phenolic hydroxyl group, 87.6g (0.42mol) of Wondamin HM as other amine compounds, and 100g of ion-exchanged water were charged and stirred until the temperature of the heat generation became constant. When the temperature stabilized, the temperature was raised to 110°C, and after confirming the outflow of water, the temperature was raised to 120°C after 30 minutes, and then the dehydration reaction was continued while raising the temperature by 10°C every 30 minutes. When the temperature reached 230°C, the reaction was continued at that temperature for 3 hours, and then the temperature was lowered by holding it under a vacuum of about 2kPa for 1 hour. Finally, an antioxidant was added to obtain a phenolic hydroxyl group-containing polyamide (a-1-1) having a mass average molecular weight of 2,800, an acid value of 0.5 mgKOH / g, an amine value of 185.8 mgKOH / g, a phenolic hydroxyl value of 25.1 mgKOH / g and a glass transition temperature of 140°C.

[0109] Separately, in a four-neck flask equipped with a stirrer, reflux condenser, nitrogen inlet tube, inlet tube, and thermometer, 284.0 g (0.49 mol in terms of dibasic acid) of Pripol 1009 as a polybasic acid compound having 36 carbon atoms, 102.7 g (0.19 mol in terms of diamine) of Priamine 1074 as a polyamine compound having 36 carbon atoms, and 100 g of ion-exchanged water were charged and stirred until the temperature of the heat generation became constant. When the temperature stabilized, the temperature was raised to 110°C, and after confirming the outflow of water, the temperature was raised to 120°C after 30 minutes, and then the dehydration reaction was continued while raising the temperature by 10°C every 30 minutes. When the temperature reached 230°C, the reaction was continued at that temperature for 3 hours, and then the temperature was lowered by holding it under a vacuum of about 2 kPa for 1 hour. Finally, an antioxidant was added to obtain polyamide (a-2-1) having a C20-60 hydrocarbon group with a mass average molecular weight of 8,800, an acid value of 87.4 mg KOH / g, an amine value of 0.3 mg KOH / g, and a glass transition temperature of -30° C. Of the total monomers used in the reaction (100 mol %), the compound having a C20-60 hydrocarbon group accounted for 51 mol %.

[0110] A phenolic hydroxyl group-containing polyamide (a-1-1) and a polyamide (a-2-1) having a C20-60 hydrocarbon group were mixed in a mass ratio of 30:70, and toluene was added to obtain a polyamide resin solution with a solid content of 40%.

[0111] (Synthesis Examples 5 and 6) Comparative Polyamides 1 and 2 Solutions of comparative polyamides 1 and 2 were obtained in the same manner as in Synthesis Example 1, except that the compositions and charged amounts were changed to those in Table 1. Comparative polyamide 1 is a polyamide having no phenolic hydroxyl group, and comparative polyamide 2 is a polyamide having no C20-60 hydrocarbon group.

[0112] The resulting polyamide resin is shown in Table 1. [Table 1]

[0113] The abbreviations in Table 1 are as follows: Pripol 1009: Croda Japan, contains C36 dimer acid and a compound with one C6 ring structure (acid value: 195 mg KOH / g) Priamine 1074: Croda Japan, C36 dimer diamine, contains a compound with one C6 cyclic structure (amine value: 210 mg KOH / g) 5-HIPA: 5-hydroxyisophthalic acid Wondamin HM: 4,4'-diaminodicyclohexylmethane, manufactured by New Japan Chemical Co., Ltd. HAB: 4,4'-diamino-3,3'-dihydroxybiphenyl MXDA: Metaxylenediamine

[0114] <Synthesis of polyester> (Polyester Resin 1) In a four-neck flask equipped with a stirrer, reflux condenser, nitrogen inlet pipe, inlet pipe, and thermometer, 25.7 parts of 5-hydroxyisophthalic acid as a polybasic acid having a phenolic hydroxyl group, 82.4 parts of adipic acid as another polybasic acid, 332.3 parts of Pripol 2033 as a polyol having a carbon number of 36, and 139.3 parts of toluene were charged, and the mixture was heated to 60°C while stirring under a nitrogen stream to dissolve uniformly. Next, 0.77 parts of tetrabutyl orthotitanate was added as a catalyst and reacted at 110°C for 3 hours. Thereafter, the temperature was raised to 230°C, and the mixture was maintained for 1 hour under a vacuum of about 2 kPa, and then reacted for a further 2 to 3 hours under a vacuum of about 1 kPa. Finally, an antioxidant and toluene were added to obtain a solution of phenolic hydroxyl group-containing polyester resin 1 having a mass average molecular weight of 9,600, an acid value of 23.4 mg KOH / g, a phenolic hydroxyl value of 18.0 mg KOH / g, a glass transition temperature of 34°C, and a solid content of 40%.

[0115] <Production of bonding paste> [Example 1] 91 parts of metal particles B1, 8.55 parts of dihydroterpineol, and 0.45 parts of polyamide A-1-1 solution (0.20% by mass based on the mass of metal particles B1) were mixed using a planetary stirrer to prepare a bonding paste.

[0116] [Examples 2 to 24], [Comparative Examples 1 to 8] A bonding paste was obtained in the same manner as in Example 1, except that the blended composition was changed according to the contents of Tables 2 to 4.

[0117] <Evaluation of bonding paste> A bonded body was produced using the obtained bonding paste in the following manner, and the obtained bonded body was used to carry out the following evaluations. The results are shown in Tables 2 to 4.

[0118] [Preparation of junction] Each bonding paste was applied once to the plated surface of the substrate 1 described below, and then the plated surface of the substrate 2 described below was placed facing the bonding paste surface and sintered by heating to obtain a bonded body. The substrate, coating conditions, and sintering conditions are shown below. 《Base material》 Substrate 1 (first bonded body): Gold-plated copper substrate (20 x 20 x 3 mm) Substrate 2 (second bonded body): Gold-plated SiC chip (5 x 5 x 0.3 mm) <Application conditions> Metal mask: 4mm square opening, 50μm thickness (manufactured by Celia Corporation) Metal squeegee: 40mm x 250mm, thickness 1mm (manufactured by Celia Corporation) Sintering conditions The provisionally bonded body was placed in a hot air oven, and the temperature was raised from 25° C. to 300° C. at a rate of 2° C. / min. After reaching 300° C., the temperature was maintained at that temperature for 2 hours.

[0119] [Bonding strength (initial, after thermal cycle test) The initial bond strength (die shear strength) of the bonded body was measured. The bonded body was then subjected to a thermal cycle test, and the bond strength after the thermal cycle was measured in the same manner as the initial bond strength. The bond strength measurement method and thermal cycle test method are described below. The adhesive strength was evaluated based on the following evaluation criteria. The higher the adhesive strength value, the better the adhesive strength. <Method of measuring bonding strength> Measurement equipment: Universal bond tester (Daisi Japan Co., Ltd., 4000 series) Measurement height: 100μm Measurement speed: 500μm / s Specifically, the substrate 1 was fixed, and the interface between the substrate 1 and the bonding paste was pushed toward the substrate 2 at a height of 100 μm at a speed of 500 μm / s, and the bonding strength at which the bond was destroyed was determined.

[0120] <<Cold-heat cycle test method>> The bonded body was kept at -40°C for 30 minutes, then kept at 25°C for 15 minutes, and then kept at 150°C for 30 minutes, which constituted one cycle, and 500 cycles were performed.

[0121] Evaluation Criteria S: Bond strength is 30 MPa or more (very good) A+: Bond strength is 22MPa or more and less than 30MPa (good) A: Bond strength is 15MPa or more and less than 22MPa (fairly good) B: Bond strength is 10MPa or more and less than 15MPa (practical) C: Bond strength is less than 10 MPa (not practical)

[0122] [Coatability] Each bonding paste was applied to a substrate 1 (gold-plated copper substrate (20×20×3 mm)) under the following application conditions, and the suitability of application was judged according to the following criteria. <Application conditions> Metal mask: 4mm square opening, 50μm thickness (manufactured by Celia Corporation) Metal squeegee: 40mm x 250mm, thickness 1mm (manufactured by Celia Corporation) Evaluation Criteria A: The bonding paste is evenly applied over the entire opening (4 mm square) (good). B: The bonding paste is applied to a part of the opening (2 mm or more and less than 4 mm square) (practical) C: The bonding paste can only be applied to a part of the opening (less than 2 mm square), or the applied part is cracked (not practical).

[0123] [Table 2]

[0124] [Table 3]

[0125] [Table 4]

[0126] As shown in Tables 2 to 4, the bonding paste of the present invention had high initial bonding strength and was able to suppress a decrease in bonding strength after a thermal cycle test, even when the adherend was a material with a small linear expansion coefficient and rigidity, such as silicon carbide. The bonding paste of the examples also had excellent coatability. In particular, when metal particles B1 having d1 in the range of 50 to 150 nm and d99 in the range of 350 to 600 nm were used, excellent initial bonding strength and bonding strength after a thermal cycle were shown. On the other hand, the bonding paste of the comparative example was inferior in bonding strength and coatability, particularly after the thermal cycle test.

Claims

1. A bonding paste comprising: a polyamide (A) which is a polymer of a polybasic acid monomer and a polyamine monomer and has a phenolic hydroxyl group in a side chain; metal particles (B); and a dispersion medium (C), The polyamide (A) satisfies the following (i) and / or (ii), The bonding paste, wherein the metal particles (B) are particles having a particle diameter (d50) corresponding to 50% of the cumulative particle diameter distribution of 100 to 350 nm. (i) The polyamide (A) is a polyamide (A-1) in which the phenolic hydroxyl group and the hydrocarbon group having 20 to 60 carbon atoms (but excluding the aromatic ring to which the phenolic hydroxyl group is bonded) are contained within the same polymer. (ii) The polyamide (A) is a polyamide (A-3) which is a mixture of a polyamide (a-1) having a phenolic hydroxyl group in a side chain and a polyamide (a-2) having a hydrocarbon group having 20 to 60 carbon atoms.

2. The bonding paste according to claim 1, wherein the content of the polyamide (A) is in the range of 0.01 to 1.70 mass% based on the mass of the metal particles (B).

3. The metal particles (B) have a particle diameter (d1) corresponding to 1% of the cumulative particle diameter distribution of 30 to 200 nm, and a particle diameter (d99) corresponding to 99% of the cumulative particle diameter distribution of 300 to 900 nm. The joining paste according to claim 1 or 2.

4. The bonding paste according to any one of claims 1 to 3, wherein the metal particles (B) have a mass reduction rate of 0.5 to 7.0 mass%.

5. A bonded body in which a first object to be bonded and a second object to be bonded are bonded with the bonding paste according to any one of claims 1 to 4.

6. A method for producing a bonded body, comprising applying the bonding paste according to any one of claims 1 to 4 to a first body to be bonded, and placing a second body to be bonded on the applied surface.

Citation Information

Patent Citations

  • Joining material and joining method using the same

    JP2011080147A

  • Binding agent and article bound by binding agent

    JP2017137375A

  • Thermosetting resin composition for thermal conductive material and cured product of the same, electronic component and electronic apparatus

    JP2020200454A

  • Heat-curable resin composition, polyamide, adhesive sheet, cured article, and printed wiring board

    WO2016001949A1